Prasyarat Sertifikasi Halal Dalam Manajemen Produksi Pada Home Industry Bakso Barokah Di Dusun Kayen Kayangan Jombang Perspektif Etika Bisnis Islam - Ahmad Khayat Tudin; Azizah, Ninik (Irtifaq, 2025)
This study examines the implementation of halal certification prerequisites in production management at Bakso Barokah Home Industry in Kayen Hamlet, Kayangan, Jombang, in the perspective of Islamic business ethics. In the midst of increasing Muslim awareness of the importance of halal consumption, halal certification is a crucial legal instrument as stipulated in Law Number 33 of 2014. However, at the micro and small business level, the process of implementing this certification often faces various challenges, both administrative, technical and socialization. This study uses a juridical-empirical approach with data collection techniques through observation, interviews, and field documentation. The results showed that business actors have moral and spiritual awareness of the importance of halal products, but have not been able to fulfill all formal requirements set by the halal certification authority, especially in the aspects of raw material documentation, supply legality, and production traceability. Of the five indicators of Islamic business ethics of the halalness of raw materials, production processes, worker welfare, product quality, and social responsibility, only two are adequately met. This lack of formal standards is rooted in limited knowledge, access to information, and cost constraints. This research recommends the need for synergy between business actors, government, and religious institutions to provide intensive education and assistance. The implementation of Islamic business ethics not only strengthens the spiritual integrity of business actors, but also becomes the foundation for legal, ethical, and competitive business sustainability in the national and global halal market. Keyword: Halal Certification, Islamic Business Ethics, Micro and Small Enterprises (MSEs)